FINANCIAL STATEMENT FRAUD DETECTION USING PERSPECTIVE OF FRAUD TRIANGLE ADOPTED BY SAS NO. 99 - Shabrina Prasmaulida (Asia Pacific Fraud Journal, 2016)
Financial statements generally aim to provide information about the company’s financial position, performance, and cash flows to the interested parties. The motivation to gain trust from the users, especially investors, shareholders and creditors, leads someone to commit fraud in the financial reporting. This study aims to detect and predict financial statement fraud based on the perspective of fraud triangle adopted by SAS No. 99. The dependent variable in this study is financial statement fraud which is proxied by earnings management, while the independent variables in this study are financial stability pressure, personal financial need, ineffective monitoring, effective monitoring, external pressure, and financial targets.Population of this research is manufacturing companies listed in Indonesia Stock Exchange period 2012 - 2014. Samples are selected using purposive sampling method and obtained 150 companies out of a total population of 162 companies. The results show that financial stability pressure and external pressurehave significant positive effect on financial statement fraud. Meanwhile, personal financial need, ineffective monitoring, effective monitoring, and financial targets do not have significant effect on financial statement fraud.